WORLD AND UZBEK EXPERIENCE IN DEVELOPMENT OF ECOLOGIC TOURISM - Safarovich, Yarashev Kuvondiq; Yusupovich, Khasanov Jasur; qizi, Qurbonova Iroda Zafar (The journal of contemporary issues in business and government, 2021)
This article covers the experience of ecological tourism in the world and Uzbekistan, the Great Silk Road, UNESCO, green economy, "International Year of Ecotourism", the 99th session of the UNWTO Executive Board (Samarkand).